DAMPAK IMPLEMENTASI BASEL III TERHADAP PERMODALAN PADA BANK DI INDONESIA (STUDI KASUS PADA PT BANK NEGARA INDONESIA (PERSERO) TBK) - Mohammad Bonnario (Sekolah Tinggi Manajemen IMMI Jakarta, 2018)
The purpose of this study is to measure Bank's ability to implement the Basel III and what strategies should be undertaken by Bank to meet the regulations and support business growth in terms of capital. This study uses secondary data by using the implications of the basel III on Bank capital and capital adequacy rate with the object of PT. Bank Negara Indonesia (Persero) Tbk. Results There are significant changes of BNI KPMM prior to using basel II and after using Basel III ie changes in presentation templates, post changes and movements, changes in total capital and CAR, and additional buffers. However, it is able to contribute greatly to its business, among others, BNI is still able to cover the massive withdrawal from DPK due to capital and loan growth provide large space for credit expansion through good LLL, as well as capital ability to support profit growth supported from percentage of capital. But with so many risks that accompany it and the turbulent business climate and additional buffers, BNI still have to increase its capital again to be able to support the aggressive BNI business.